2017
DOI: 10.33549/physiolres.933552
|View full text |Cite
|
Sign up to set email alerts
|

Glucose Added to a Fat Load Suppresses the Postprandial Triglyceridemia Response in Carriers of the 1131C and 56G Variants of the APOA5 Gene

Abstract: Apolipoprotein A-V plays an important role in the determination of plasma triglyceride (TG) concentration. We aimed to determine whether polymorphisms -1131T>C (rs662799) and 56C>G (rs3135506) of the APOA5 gene have an impact on the course of postprandial lipemia induced by a fat load and a fat load with added glucose. Thirty healthy male volunteers, seven heterozygous for the -1131C variant and three for the 56G variant (HT) carriers, and 20 wild-type (WT) carriers underwent two 8-hour tests of postpran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…This fact could be related to the lack of response to insulin and HOMA-IR in patients carrying the C allele in our study after the dietary intervention. In agreement of this hypothesis, recent investigations in Caucasian healthy subjects [33] reported that this SNV modulated postprandial lipidemia after a breakfast containing 75 g of fat, though the addition of glucose (25 g) to the tested breakfast suppressed this change. Perhaps, the secretion of insulin after a glucose overload could explain these findings, because insulin action was shown to decrease APOA5 expression and even to downregulate ApoA-5 levels in plasma [34].…”
Section: Discussionsupporting
confidence: 74%
“…This fact could be related to the lack of response to insulin and HOMA-IR in patients carrying the C allele in our study after the dietary intervention. In agreement of this hypothesis, recent investigations in Caucasian healthy subjects [33] reported that this SNV modulated postprandial lipidemia after a breakfast containing 75 g of fat, though the addition of glucose (25 g) to the tested breakfast suppressed this change. Perhaps, the secretion of insulin after a glucose overload could explain these findings, because insulin action was shown to decrease APOA5 expression and even to downregulate ApoA-5 levels in plasma [34].…”
Section: Discussionsupporting
confidence: 74%
“…Located in the promoter region of APOA5 gene, -1131T>C (rs662799) might lower apo AV levels by down-regulating APOA5 mRNA translation [134]. [131] all report significantly greater postprandial triglyceride increases in carriers of the C allele than in TT homozygote. Fig 3A-3C illustrate quantile-dependent expressivity for APOA5 genetic variants.…”
Section: Resultsmentioning
confidence: 99%
“…This situation could be implied in the lack of response of insulin and HOMA-IR in patients carrying the C allele in our study after dietary intervention. In a recent study in healthy volunteers [33], T allele carriers had higher postprandial lipidemia after an experimental breakfast of 75 g of fat, though the addition of glucose (25 g) to the test suppressed this difference. Perhaps secretion of insulin after glucose overload plays a role in these observations, because insulin action was shown to downregulate APOA5 expression and even to decrease ApoA-5 levels in plasma [34].…”
Section: Disease Markersmentioning
confidence: 90%